Kidney immune status and blood microcirculation alterations under treatment of purulent pyelonephritis - Yuliia G. Chernova; Aleksandr I. Neimark; Irina N. Tarasova; Galina A. Nitievskaia (LLC "MEDIAFORMAT", 2021)
Aim. To assess alterations of immune status and blood microcirculation in patients with purulent pyelonephritis during treatment. Methods. The prospective cohort multiple randomized controlled trial was carried out at the Department of Urology and Andrology at the Municipal Hospital No. 11 (Barnaul) in 2016-2019. A total of 94 patients aged 20-60 diagnosed with purulent pyelonephritis were treated during this period. The study was approved by the Ethics Committee of the Altai State Medical University (protocol No. 14 dated November 18, 2016). The informed consent was submitted by all participants. During the study, two groups were formed, which included patients already diagnosed with purulent pyelonephritis and patients with a suspicion on purulent process based on clinical, laboratory and functional tests data. The patients were randomized and divided into two groups in accordance with the methods used. The first group, showing no clinical and laboratory response to therapy, underwent surgery (n=47), the second group received cryoprcipitate together with standard conservative treatment for purulent pyelonephritis (n=47). All the cohorts were similar in age, gender and ethnicity. The patients' immune status was estimated: IgM, IgG and IgA-based enzyme immunoassay tests were performed using the Immunoscreen-G, M, A-EIA-BEST kit by Vector-Best (Novosibirsk); serum interleukin-1β, interleukin-6, TNF-α and urine interleukin-8 levels were assayed using the Interleukin-8-EIA-BEST, Interleukin-1β-EIA-BEST, Alpha-TNF-EIA-BEST and Interleukin-6-EIA-BEST kits (Vector-Best, Russia, 2011). In addition to a number of instrumental tests, blood microcirculation in the zone of inflammation was assessed using the LAKK-2 analyzer in the projections of kidneys. The immune status markers were assessed upon admission and on day 6-7 of hospital stay. Each and every patient received complex conservative treatment. The patients received antibacterial therapy during an average of 3-4 days after their body temperature was back to normal. Results. Immune status assessment in group 1 patients revealed multidirectional alterations in immunoglobulin levels: significantly increased level serum Ig G and Ig M and decreased level of Ig A indicated the impaired humoral immunity. On day 9 of treatment the patients of group 1 still showed decreased level of Ig A. Their Ig G became even higher, and the level Ig M showed a decreasing trend. Upon admission, the serum levels of proinflammatory cytokines in patients of group 1 were more than twice as high as the control level, which could be considered the natural consequence of the observed infectious process in the urinary tract. On day 9 of treatment serum levels of proinflammatory cytokines became significantly lower: urine IL-8 level declined to 10.01±0.86 pg/mL, blood IL-6 level declined to 12.04±0.81 pg/mL, IL-1 level declined to 10.67±1.07 pg/mL, and TNF-α level declined to 4.75±0.40 pg/mL. However, the latter failed to reach the physiologically normal level, which indicated the incomplete reversal of inflammation in the urinary tract against the background of using the selected treatment approach. Blood microcirculation assessment using Laser Doppler flowmetry (LDF) prior to prescribing therapy to patients of group 1 revealed the following basal blood flow indicators: decreased shunt blood flow, reduced average blood flow, index of microcirculation efficiency, myogenic tone and fluctuations in erythrocyte flow, as well as elevated coefficient of variation and neurogenic tone compared to control and comparison groups. After surgery used as an adjunct to the complex treatment the significantly increased index of microcirculation efficiency, elevated average blood flow, increased neurogenic tone, reduced shunt blood flow and myogenic tone were observed. The listed indicators showed a positive trend, but failed to reach the physiologically normal level. Kidney inflammation persisted despite surgical and antibacterial treatment. Group 2. Assessment of group 2 patients prior to prescribing drug therapy revealed the pronounced serum immunoglobulin level alterations. Serum Ig G and Ig M levels were increased compared to control group, and the Ig A level was decreased, which indicated the humoral immunity impairment. Assessment of immunoglobulin levels after treatment showed they were back to normal, which indicated complete restoration of humoral immune response. In patients of group 2, cytokine profile analysis was performed prior to prescribing drug therapy supplemented by cryoprcipitate, and on day 9 of treatment. Thus, prior to complex treatment, the patients' serum and urine levels of proinflammatory cytokines were more than twice as high as the control level, which was due to ongoing inflammatory process, and the urine IL-8 level was twice as high as the control level. Drug therapy with the use of cryoprcipitate resulted in recovery of IL-1β, TNF-α, IL-6 and IL-8 levels to physiologically normal levels obtained by examination of healthy individuals. This indicates complete reversal of inflammation in the urinary tract against the background of using the selected treatment approach. Assessment of microcirculation in the surface projections of kidneys by LDF revealed alterations in basal blood flow similar to those observed in patients of group 1. The average blood flow, shunt blood flow, neurogenic tone and index of microcirculation efficiency decreased significantly, and the myogenic tone increased. On day 9 of treatment the significantly increased average blood flow, index of microcirculation efficiency, neurogenic tone and shunt blood flow were observed. Myogenic tone dropped to physiologically normal level. Based on the alterations observed, the improved blood circulation in the ischemic zone and reduced hypoxia in the affected area of the kidneys can be reported.